Ten year results following HTO - analysis of clinical outcome and survival rates in terms of TKA revision. Issue 9 (28th September 2020) - Bode, Lisa; Brenner, Anna-Sophie; Eberbach, Helge; Kloos, Ferdinand; Niemeyer, Philipp; Schmal, Hagen; Bode, Gerrit
Introduction: Varus deformity is a well-known risk factor for focal cartilage defects and even medial osteoarthritis of the knee due to increase of medial compartment peak pressure. High tibial osteotomy using angular-stable implants is an effective and standardized method unloading the medial compartment and resulting in pain reduction and excellent clinical follow-up. Until now only mid-term results have been published and little is known concerning conversion to total knee arthroplasty (TKA). Purpose of the present study is to examine long-term results with special focus on TKA convesion. Hypotheses: HTO results in good to excellent results in terms of functional outcome and TKA conversion even after ten years. Methods: All patients aged 18 – 65 years and treated with HTO due to focal cartilage lesions of the medial compartment or medial gonarthritis with underlying varus deformity between 01.01.2004 and 31.12.2013, were included in the present study. Lysholm score and visualized analog scale (VAS) were obtained pre- and postoperatively while Knee Osteoarthritis and Outcome Sccore (KOOS) and IKDC and TKA conversion rate were obtained postoperatively only. Statistical analysis was performed using SPSS Software 24.0 (IBM Corp. Armonk, USA). Results: 125 patients with a mean age of 44, 4 +- 10, 17 (Range 18, 9 - 66, 9) years were included in the present study. Mean follow-up (FU) was 118, 4 +- 27, 3 (Range 73, 0 - 171) months. Lysholm score and VAS significantly improved at FU in comparison to preoperative valus. Patients presented good functional outcom even after ten years (KOOSpain 82, 9 +- 14, 4; KOOS symp 78, 6+-17, 6, KOOS adl 87, 8+-13, 3; KOOSsport 53, 1+#30, 4; KOOSQOL 70, 2+-21, 4;KOOS4 71, 2+-18, 2). Patients requiered TKA conversion in 12.8%, resulting in 87.2% TKA free survival-rates ten years after HTO implantation. Conclusion: HTO is a safe and effective method resulting in good functional outcome and low conversion rates to TKA even after ten years.